ANALISIS KEMAMPUAN KONEKSI MATEMATIS DAN MOTIVASI BELAJAR SISWA KELAS VIII DI SMP AN-NAJA BANDUNG BARAT - Siti Qotbiyah (Journal on Education, 2018)
Mathematics as one of the school subjects cannot be separated from other scientific disciplines and problems in everyday life. Mathematical connection is one of the standard processes. Through mathematical connections between material and other material students can reach several aspects to solve mathematical problems. The research method used is descriptive qualitative. There are samples in this study that are grade VIII students of high, medium, and low abilities in MTs, West Bandung Regency. The connection ability test instruments were given as many as 5 questions accompanied by questionnaires for each student. Then the results obtained are the level of mathematical connection ability and learning motivation of MTs students in West Bandung Regency based on written tests and the results of questionnaires with students are still relatively poor. Furthermore, this research is part of the thesis that I will examine.